2018
DOI: 10.1371/journal.pone.0193638
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive predictors of cervical cancer screening’s stages of change among sample of Iranian women health volunteers: A path analysis

Abstract: IntroductionThe uptake of Pap smear among Iranian women is low, resulting in a high rate of casualties from cervical cancer in Iran. The present study used the Health Belief Model (HBM) and the Stages of Change theory as theoretical frameworks for understanding the predictors of the behaviour of Iranian Women Health Volunteers (WHVs) with respect to cervical cancer screening.MethodsData from the 1,253 WHVs were analyzed using path analysis to assess the effects of cognitive factors (including knowledge, percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…The significant mediation effect by perceived seriousness of cervical cancer on the link between cervical cancer knowledge and screening practices has been reported by some researchers [19, 21]. This finding is however, inconsistent with previous works which found most of the health belief model constructs to be significant mediators of the link between cervical cancer knowledge and screening practices [20] The inconsistency may be due to the composition of the sample size as the current study was among female university students as against a community-based sample.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The significant mediation effect by perceived seriousness of cervical cancer on the link between cervical cancer knowledge and screening practices has been reported by some researchers [19, 21]. This finding is however, inconsistent with previous works which found most of the health belief model constructs to be significant mediators of the link between cervical cancer knowledge and screening practices [20] The inconsistency may be due to the composition of the sample size as the current study was among female university students as against a community-based sample.…”
Section: Discussionmentioning
confidence: 67%
“…Evidence abound in health promotion and education literature on the impact of health belief constructs on screening behaviours among different populations. For examples, studies have found perceived susceptibility, perceived seriousness and perceived benefits of cervical cancer screening to be key determinants of cervical cancer screening practices [13, 18, 20, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this case, the findings of a study conducted in different settings indicated that there was low uptake of cervical cancer screening services [9][10][11][12][13][14]. Lack of awareness, poor attitude towards cervical cancer screening, and poor perception of the severity of the disease were some of the factors for not up taking the screening service.…”
Section: Introductionmentioning
confidence: 99%
“…We have incorporated into the wireless queuing device an App that included a risk survey, finding that women with high perceived susceptibility were those who underwent cytology after being exposed to a ‘Tu Turnero ESE ‘. Other studies have already documented, based on the Health Belief Model, that factors such as perceived benefits, perceived susceptibility, perceived severity/seriousness, and perceived barriers median the relationship between cervical cancer knowledge and screening behaviours [ 100 102 ].…”
Section: Discussionmentioning
confidence: 99%